Caudal regression syndrome in a fetus of a glucokinase‐maturity‐onset diabetes of the young pregnancy. Issue 2 (30th January 2019) - Taylor, R. A. M.; Mackie, A.; Mogra, R.; Pinner, J.; Rajendran, S.; Ross, G. P.
Abstract: Background: Glucokinase‐maturity‐onset diabetes of the young (GCK‐MODY) is a form of diabetes caused by heterozygous inactivating mutations in the GCK gene. Affected individuals maintain their fasting glucose levels at a higher set point (5.4–8.3 mmol/l) than the general population. Hyperglycaemia in women with Type 1 or Type 2 diabetes is known to confer increased risk of fetal congenital abnormalities. The association between GCK‐MODY and congenital abnormalities, however, remains uncertain. Case report: A 35‐year‐old woman in her third pregnancy was diagnosed with gestational diabetes at 13 weeks' gestation (fasting blood glucose 6.0 mmol/L, 1‐h blood glucose 9.2 mmol/l, 2‐h blood glucose 7.3 mmol/l). The morphology scan at 19+2 weeks' gestation showed a Type III sacral agenesis. The woman elected to terminate the pregnancy. Her postpartum oral glucose tolerance test was suggestive of GCK‐MODY (fasting blood glucose 7.4 mmol/l, 1‐h blood glucose 9.3 mmol/l, 2‐h blood glucose 7.3 mmol/l). Mutation analysis of the GCK gene identified a novel heterozygous GCK missense mutation, p.V199M, classified as likely pathogenic, providing molecular confirmation of the suspected GCK‐MODY diagnosis. Discussion: Sacral agenesis is a rare form of sacral abnormality affecting 0.005% to 0.1% of pregnancies. It is a subtype of the caudal regression sequence, a cardinal feature of diabetic embryopathy. This case raises the question as to whether hyperglycaemia in GCK‐MODY may increase the risk of fetal caudal regression syndrome as reported in women with pre‐existing diabetes mellitus. Improved diagnostic rates of GCK‐MODY, and MODY registers that include pregnancy outcomes, are important to further elucidate risk of congenital abnormalities in GCK‐MODY. What's new?: The association between maternal glucokinase‐maturity‐onset diabetes of the young (GCK‐MODY) in pregnancy and fetal congenital abnormalities is unclear. This report describes a case of sacral agenesis in the fetus of a woman who was subsequently diagnosed with a novel GCK‐MODY mutation. The case raises the question as to whether hyperglycaemia in GCK‐MODY may increase the risk of caudal regression syndrome as reported in people with pre‐existing diabetes mellitus.